Environmental and toxicological assessment of the water quality of Burshtynska TPP cooling reservoir - T. L. Rychak; L. M. Arkhypova (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія)
Purpose. Determination of the ecological and toxicological assessment of the water quality of the cooling reservoir of the Burshtyn TPP, which is a component of the Galicia National Nature Park.